Scientific research program "Sources for Croatian heritage and Croatian European identity" - Boras, Damir (2007)
History and identity of Croatian people can be viewed through written and material heritage accumulated over centuries onwards on one side and heritage that emerges at this moment on the other side. // Scientific research projects gathered inside the program (Croatian dictionary heritage and Croatian European identity, Sources for early modern Croatian history, Ethnological database as a knowledge source for ethnical and national identities, Encyclopedic film dictionary) using multidisciplinary approach gather data of Croatian heritage, written and material, and tend to transform written heritage into machine readable form which will enable easier access to older Croatian written documents. The process will open up, still restricted, Croatian heritage for further research and start the process of creating database of material and written heritage locations as a basis of Croatian national identity. Existence of Croatian lexicography and encyclopedica in European science from 16th century witnesses continuation and acceptance of Croatian language and Croatia as a vital part of European identity. // Croatia's' integration in Europe can also be seen in numerous sources of Croatian historical documentation in various cultural institutions all around Europe. Bibliographical lexicon will list less known sources for researching Croatian national history outside Croatia and make them available for future research. // Researches of current and future involvement of Croatia in Europe tend to produce future Croatian heritage through lexicographical analysis of philosophical terminology and creation of encyclopedic cinematography terminology. Research will, in ethnological database also list sources for research of ethnological movements in Croatia, and therefore also in Europe.